Super-coarsening process of printed circuit board and super-coarsening liquid medicine

By performing super-coarse treatment on the printed circuit board in two times and using tannin acid and chitosan to form a film layer in the second treatment, the problem of insufficient copper surface binding force in the prior art is solved, and a higher copper surface binding force and a more uniform rough structure are achieved.

CN119521569APending Publication Date: 2025-02-25SHENZHEN DAZHENG RUIDI TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411674203.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing ultra-coarse technology still has limited effect on improving the bonding force of copper surface, and it is difficult to fully meet the performance requirements of high-end products.

Method used

The process scheme of super-coarse treatment was adopted in two times. The first time was used to wash water and pickle with super-coarse medicine, and the second time was used to wash tannin acid and chitosan mixed modification solution, and the film layer was formed by cross-linking of glutaraldehyde.

Benefits of technology

Through two super-coarse treatments and pickling, the bonding force of the copper surface is significantly improved, forming a more uniform rough structure, meeting the performance requirements of high-end products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of printed circuit boards, and particularly discloses an ultra-coarsening process of a printed circuit board and an ultra-coarsening liquid medicine. According to the invention, the printed circuit board is subjected to super-roughening treatment twice, acid pickling is carried out between the two times of super-roughening treatment, and tannic acid and chitosan are used as film forming components together during the second time of super-roughening treatment. After the ultra-roughening process is completed, the copper surface binding force of the formed film layer is fully improved, the defects in the related technology are overcome, and the performance requirements of high-end products can be better met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of printed circuit boards, and more specifically, to an ultra-roughening process and ultra-roughening solution for printed circuit boards. Background Art

[0002] With the rapid development of the printed circuit board industry, the circuits of printed circuit boards are becoming more and more dense, and the process precision is constantly improving, so the process requirements for circuit boards are getting higher and higher. Printed circuit boards use photochemical pattern transfer technology and solder mask technology, and how to improve the bonding strength of the copper surface (generally refers to the bonding strength between the copper surface and the solder mask ink coating) is the key to ensuring the quality of the photochemical pattern transfer process and the solder mask process. Traditional pre-treatment processes often use medium coarsening, roller brushing, diamond sandblasting, volcanic ash grinding, sulfuric acid and sodium persulfate micro-etching to treat the copper surface, but the effect of traditional pre-treatment processes is difficult to meet the current high-end product needs.

[0003] The ultra-roughening process is a new type of treatment process. By using a special ultra-roughening solution and the corresponding process flow, the copper surface can be slightly and evenly etched, changing the copper surface morphology, increasing the overall contact area of ​​the copper surface, and forming a micro-honeycomb rough structure. It can better improve the copper surface bonding strength than traditional processes. For current high-end circuit board products, the industry generally requires the use of ultra-roughening technology.

[0004] With respect to the above-mentioned related technologies, the inventors believe that the current ultra-roughening process still has a limited effect on improving the bonding strength of the copper surface and is difficult to fully meet the performance requirements of high-end products. Summary of the invention

[0005] In the related art, the effect of the ultra-roughening process on improving the bonding strength of the copper surface is still relatively limited, and it is difficult to fully meet the performance requirements of high-end products. In order to improve this defect, the present application provides an ultra-roughening process and ultra-roughening solution for a printed circuit board.

[0006] In a first aspect, the present application provides a super-roughening process for a printed circuit board, which adopts the following technical solution: A super-roughening process for a printed circuit board comprises the following steps: (1) Wash the circuit board with water, then spray the super-roughening solution on the circuit board at 35-45°C, the spraying time is controlled to be 30-120s, and then wash the circuit board to remove the super-roughening solution; in this step, the components of the super-roughening solution include organic copper, formic acid, sodium formate, sodium chloride, a wetting agent, a leveling agent and a regulator; (2) Spray hydrochloric acid on the circuit board, and then wash away the hydrochloric acid on the circuit board with water; (3) Add tannic acid and chitosan to water and dissolve them together, and then mix them with the super-roughening solution of step (1) to obtain a mixed modified solution; immerse the circuit board in the mixed modified solution at 25-35° C., then take it out and dry it, then add the circuit board to glutaraldehyde solution for cross-linking, and then take the circuit board out again and dry it to complete the super-roughening of the printed circuit board.

[0007] By adopting the above technical scheme, the present application first uses super-roughening solution to carry out the first super-roughening treatment on the circuit board, and then washes and pickles. After washing away the hydrochloric acid, the super-roughening solution is mixed with tannic acid and chitosan, and the circuit board is further super-roughened for the second time with the obtained mixed modified liquid, and then cross-linked and cured using glutaraldehyde. Glutaraldehyde can react with chitosan and form a film layer with tannic acid. The two super-roughening treatments before and after and the pickling between the two super-roughening treatments can effectively improve the surface morphology of the printed circuit board, and also create favorable conditions for the attachment of the film layer, and the formation of the film layer can further improve the copper surface bonding strength on the basis of the super-roughening treatment, thereby overcoming the defects in the relevant technology and fully meeting the performance requirements of high-end products.

[0008] Preferably, in step (2) of the process, the concentration of hydrochloric acid used is 10-15wt%.

[0009] By adopting the above technical solution, the present application optimizes the concentration range of hydrochloric acid, which helps to fully achieve the ultra-roughening treatment of the printed circuit board.

[0010] Preferably, in step (3) of the process, oxidized microcrystalline cellulose is also mixed with the super-coarsening solution.

[0011] By adopting the above technical solution, oxidized microcrystalline cellulose can form hydrogen bonds with chitosan and tannic acid, and the surface of oxidized microcrystalline cellulose also has aldehyde groups, which can undergo a curing reaction with the amino groups of chitosan, thereby introducing oxidized microcrystalline cellulose into the film layer formed by the mixed modified liquid. The addition of oxidized microcrystalline cellulose can improve the film-forming effect of the mixed modified liquid, thereby helping to improve the copper surface bonding force.

[0012] Preferably, the oxidized microcrystalline cellulose is prepared according to the following method: Distilled water and sodium periodate are mixed, acidified with sulfuric acid, and then microcrystalline cellulose is added. After being protected from light, the mixture is heated in a water bath while being stirred. After the reaction is completed, ethylene glycol is added, and the unreacted sodium periodate is removed after continued stirring. The mixture is then filtered, and the product is washed with water and dried. The product is then ground and sieved to obtain oxidized microcrystalline cellulose.

[0013] By adopting the above technical solution, the present application uses sodium periodate as an oxidant in an acidic environment to oxidize microcrystalline cellulose, the six-membered ring in the microcrystalline cellulose is opened, and an aldehyde group is formed at the opening position, thereby obtaining oxidized microcrystalline cellulose.

[0014] Preferably, the microcrystalline cellulose is pretreated according to the following method before use: Weigh microcrystalline cellulose, add it into sodium hydroxide solution and mix it, stir it under heating in a water bath, then filter it and wash it with deionized water, dry the obtained powder, grind it and sieve it, so as to complete the pretreatment of microcrystalline cellulose.

[0015] By adopting the above technical scheme, the present application uses sodium hydroxide to carry out swelling pretreatment on microcrystalline cellulose, so that the crystalline area of ​​​​the microcrystalline cellulose is broken and the grain size is reduced. At the same time, the aggregated structure of the microcrystalline cellulose molecules is also opened, and the active groups are exposed to the outside, which significantly improves the reactivity of the microcrystalline cellulose. After the above pretreatment, an oxidized microcrystalline cellulose with richer aldehyde groups and easier to cross-link with chitosan can be obtained. This oxidized microcrystalline cellulose can further improve the film-forming effect of the mixed modified liquid, thereby helping to improve the copper surface binding force.

[0016] Preferably, in step (3) of the process, cyclodextrin polymer is also mixed with the ultra-roughening solution.

[0017] By adopting the above technical solution, the cyclodextrin polymer is a polymer polymerized with cyclodextrin as a structural unit, and contains a large number of hydroxyl groups in the molecule, which can form a strong hydrogen bond with tannic acid, and can also form hydrogen bonds with chitosan and microcrystalline cellulose. Under the action of hydrogen bonds, the addition of cyclodextrin polymer can improve the film-forming effect of the mixed modified liquid and help improve the copper surface bonding force.

[0018] Preferably, the cyclodextrin polymer is prepared according to the following method: (1) Add cyclodextrin and sodium hydroxide to deionized water, stir to dissolve, heat in a constant temperature water bath, stir under ventilation conditions, and add epichlorohydrin. After the reaction, add acetone in an ice water bath to terminate the reaction; (2) Pour off the supernatant, wash the precipitate with acetone and ethanol in turn, then add water to dissolve the precipitate, and obtain a crude polymer after neutralization. The crude polymer is purified to obtain a cyclodextrin polymer.

[0019] By adopting the above technical solution, the present application allows epichlorohydrin to react with cyclodextrin in an alkaline environment. During the reaction, the epoxy group of epichlorohydrin will undergo a ring-opening reaction with the hydroxyl group of cyclodextrin. At the same time, the chlorine atom of epichlorohydrin will react with the hydroxyl group of cyclodextrin, removing the hydrogen chloride molecule and closing the ring to form a new epoxy group. Through multiple cycles of ring opening and ring closing reactions, a cyclodextrin polymer can be obtained.

[0020] In a second aspect, the present application provides an ultra-roughening solution, which adopts the following technical solution.

[0021] A super-roughening solution, which uses water as a solvent and includes components with the following concentrations: 30-50 g / L of organic copper, 80-150 g / L of formic acid, 28-42 g / L of sodium formate, 5-15 g / L of sodium chloride, 230-250 g / L of wetting agent, 3-5 g / L of leveling agent, and 0.1-0.2 g / L of adjusting agent.

[0022] By adopting the above technical solution, the ultra-roughening solution of the present application can produce a concave-convex roughened surface on copper and copper alloys, which is suitable for the dry film, green paint and plugging process of BGA or Flip, and can be used for the pre-treatment of chemical tin and chemical nickel gold of PCB. By adding a wetting agent, a leveling agent and a regulator, the appearance of the copper surface of the circuit board can be made uniform, the roughness can reach the expected level, and it is not easy to have problems such as uneven appearance color and excessive color difference, which effectively improves the bonding strength of the copper surface and improves the quality of the circuit board.

[0023] Preferably, the wetting agent is selected from two of sodium fatty amidoalkyl sulfate, sodium sulfated ricinoleate, sodium cycloalkane sulfate, and polyethylene imine, and the leveling agent is selected from two of polyethylene glycol carboxyl azide, mannitol, galactitol, and polyethylene glycol.

[0024] By adopting the above technical solution, the present application optimizes the composition of the wetting agent and the leveling agent. The wetting agent can adjust the hydrophilicity of the copper surface so that the liquid medicine can evenly contact the copper surface, thereby improving the permeability and dispersibility of the super-roughening solution. The copper surface of the circuit board is not a uniform and flat surface, and the density of different positions is also different. Generally speaking, the better the density, the less the bite; the worse the density, the more the bite. The above-mentioned leveling agent combination has an inhibitory effect on the bite of weak parts, and can avoid the problem of excessive etching depth of the local copper surface. Under the synergistic effect of the wetting agent and the leveling agent, the super-roughening solution can fully contact the copper surface and be evenly distributed, which helps to improve the bonding strength of the copper surface.

[0025] Preferably, the regulator is selected from one of hexadecylamine, sodium ethylenediaminetetramethylenephosphonate, and octadecylamine; and the organic copper is selected from at least one of copper propionate, copper acetate, and copper formate.

[0026] By adopting the above technical scheme, the present application preferably selects the specific types of adjusters and organic copper. The adjuster can adjust the structural characteristics of the electroplated copper surface so that the electroplated copper surface forms a dense honeycomb rough structure, avoids excessive corrosion, helps to protect the fragile positions of the copper surface, maintains the uniformity of the copper surface, and helps to improve the bonding strength of the copper surface.

[0027] In summary, this application has the following beneficial effects: 1. The present application performs super-roughening treatment on the printed circuit board twice, and uses tannic acid and chitosan as film-forming components in the second super-roughening treatment, and performs acid washing between the two super-roughening treatments. The formation of the film layer fully improves the copper surface bonding strength, overcomes the defects in the relevant technology, and enables the circuit board to better meet the performance requirements of high-end products.

[0028] 2. In the present application, oxidized microcrystalline cellulose is preferably used as an additive in the second super-roughening treatment. The addition of oxidized microcrystalline cellulose can improve the film-forming effect of the mixed modified liquid and help to improve the copper surface bonding strength.

[0029] 3. The present application preferably uses cyclodextrin polymer as an additive for the second super-roughening treatment. Cyclodextrin polymer is a polymer formed by polymerization of cyclodextrin as a structural unit. The molecule contains a large number of hydroxyl groups, which can form strong hydrogen bonds with tannic acid, and can also form hydrogen bonds with chitosan and microcrystalline cellulose. The addition of cyclodextrin polymer can improve the film-forming effect of the mixed modified liquid and help improve the copper surface bonding force.

[0030] 4. The present application optimizes the composition of the super-roughening solution. By adding a wetting agent, a leveling agent, and a regulating agent, the copper surface of the circuit board after the super-roughening process is made uniform in appearance, the roughness can reach the expected level, and it is not easy to have problems such as uneven color and excessive color difference. The bonding strength of the copper surface is greatly improved, and the quality of the circuit board is effectively improved. DETAILED DESCRIPTION

[0031] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.

[0032] The following is an explanation using Preparation Example 1.

[0033] Preparation Example 1 In this preparation example, oxidized microcrystalline cellulose was prepared according to the following method: Mix 350 mL of distilled water and 4 g of sodium periodate, adjust the pH to 6 with 20 wt % sulfuric acid, add 2 g of microcrystalline cellulose, heat in a water bath at 40 ° C after light protection, and stir at the same time. After 4 hours, the reaction is completed, add 20 mL of 0.2 mol / L ethylene glycol aqueous solution, continue stirring for 30 minutes to remove unreacted sodium periodate, then filter, wash and dry the product, grind and sieve to obtain oxidized microcrystalline cellulose.

[0034] Preparation Example 2 The difference between this preparation example and preparation example 1 is that the microcrystalline cellulose is pretreated before use, and the pretreatment method is as follows: Weigh 5.0 g of microcrystalline cellulose, add it to 100 mL of 15% sodium hydroxide solution, stir it magnetically in a 60°C water bath for 2 h, then filter it, wash it with deionized water 3 to 4 times, dry the powder at 40°C, grind it and sieve it to complete the pretreatment.

[0035] The following is an explanation using Preparation Example 3.

[0036] Preparation Example 3 In this preparation example, the cyclodextrin polymer was prepared according to the following method: (1) Add 10 g of cyclodextrin (β-cyclodextrin) and 5.34 g of sodium hydroxide to 16 mL of deionized water, stir to dissolve, and then heat in a constant temperature water bath at 30 °C. Stir at a rate of 600 rpm under ventilation conditions, and add 6.8 mL of epichlorohydrin under ventilation conditions. After 2 hours of reaction, add 60 mL of acetone in an ice water bath to terminate the reaction; (2) Pour off the supernatant, wash the precipitate with acetone and ethanol in turn, then add water to dissolve the precipitate, neutralize to pH 7 to obtain a crude polymer, and use a 10,000 molecular weight ultrafiltration tube to centrifuge and purify the crude polymer to obtain a cyclodextrin polymer. Example

[0037] In the present application, the CAS number of polyethyleneimine is 9002-98-6, and the carboxyl group of azide polyethylene glycol is N 3 -PEG1000-COOH, polyethylene glycol is PEG1000.

[0038] Examples 1-5 The following description is given by taking Example 1 as an example.

[0039] Example 1 This embodiment provides a super-roughening process for a printed circuit board, comprising the following steps: (1) Wash the circuit board with water, then spray the super-roughening solution on the circuit board at 35°C (abbreviated as T1 in Table 1), the spraying time is controlled at 30s (abbreviated as t in Table 1), and then wash with water to remove the super-roughening solution on the circuit board; (2) Spray hydrochloric acid with a concentration of 10wt% (referred to as hydrochloric acid concentration in Table 1) on the circuit board, and control the spraying time to be 60s, and then wash the hydrochloric acid on the circuit board with water; (3) Tannic acid and chitosan are added to water to dissolve them respectively, and then mixed with the super-roughening solution of step (1) to obtain a mixed modified solution with a tannic acid concentration of 100 g / L and a chitosan concentration of 35 g / L; the circuit board is immersed in the mixed modified solution at 25°C (abbreviated as T2 in Table 1) for 3 minutes, then taken out and dried at 75°C, then the circuit board is added to a 2wt% glutaraldehyde aqueous solution for cross-linking for 1 minute, and then the circuit board is taken out again and dried at 75°C to complete the super-roughening of the printed circuit board.

[0040] This embodiment also provides an ultra-roughening solution, i.e., the ultra-roughening solution used in step (1), which specifically includes the following components in concentration: 30 g / L organic copper, 80 g / L formic acid, 28 g / L sodium formate, 5 g / L sodium chloride, 230 g / L wetting agent, 3 g / L leveling agent, and 0.1 g / L adjusting agent; the organic copper is copper propionate, and the adjusting agent is hexadecylamine; the wetting agent is composed of sodium fatty acylaminoalkyl sulfate and sodium ricinoleate sulfate in a weight ratio of 4:1, and the leveling agent is a mixture of polyethylene glycol carboxyl and mannitol in a weight ratio of 1:2.

[0041] As shown in Table 1, the differences between Examples 1-5 mainly lie in the different ultra-roughening process parameters and the component concentrations of the ultra-roughening solution.

[0042] Table 1 Ultra-roughening process parameters and component concentrations of ultra-roughening solution

[0043] In addition, there are differences in the specific components used in the super-roughening solutions of Examples 1-5. The specific differences are shown in Table 2. The proportions in Table 2 are all weight ratios.

[0044] Table 2 Specific components of super roughening solution Example

[0045] The difference between this embodiment and embodiment 5 is that in step (3) of the ultra-roughening process, oxidized microcrystalline cellulose is also mixed with the ultra-roughening solution. The oxidized microcrystalline cellulose is prepared according to the method of preparation example 1, and the amount used is 20% of the total weight of chitosan.

[0046] Example 7 The difference between this example and Example 6 is that the oxidized microcrystalline cellulose is prepared according to the method of Preparation Example 2.

[0047] Example 8 The difference between this embodiment and embodiment 7 is that in step (3) of the ultra-roughening process, a cyclodextrin polymer is also mixed with the ultra-roughening solution. The cyclodextrin polymer is prepared according to the method of preparation example 3, and the amount used is 15% of the total weight of chitosan.

[0048] Comparative Example 1 In this comparative example, the components in the organic acid super-roughened aqueous solution include 10 g / L copper chloride, 80 g / L tannic acid, 30 g / L sodium acetate, 10 g / L guanidine hydrochloride, 15 g / L hydrogen peroxide, 5 g / L aminotriazole, 10 g / L triethanolamine, 1 g / L sodium silicate, 1 g / L diethylenetriamine penta (methylene phosphonic acid), 2 g / L polymethacrylic acid (average molecular weight 700); pH is 3.0, density is 1.14 g / cm 3 .

[0049] A super-roughening process for a circuit board comprises the following steps: (1) Clean the circuit board surface and wash it with water for later use; (2) Tannic acid, deionized water and chitosan are mixed and stirred to dissolve to obtain a mixed solution A; copper chloride, sodium silicate, diethylenetriamine penta (methylenephosphonic acid) and polymethyl methacrylate are added to the mixed solution A and stirred to obtain a mixed solution B; sodium acetate, guanidine hydrochloride, aminotriazole and triethanolamine are added to the mixed solution B and mixed to obtain a mixed solution C; hydrogen peroxide is added to the mixed solution C and stirred to obtain an organic acid ultra-roughened aqueous solution; (3) Soak the circuit board in an organic acid super-roughened aqueous solution at 25°C for 3 minutes, take it out and dry it at 70°C, put it in a 2wt% glutaraldehyde solution for cross-linking for 1 minute, dry it again and set it aside.

[0050] Comparative Example 2 The difference between this comparative example and Example 1 is that, in the super-roughening process, after the first water washing of the circuit board in step (1), the process directly proceeds to step (2), skipping the first step of spraying the super-roughening solution.

[0051] Comparative Example 3 The difference between this comparative example and Example 1 is that, in the ultra-roughening process, after completing step (1), step (2) is skipped and step (3) is directly entered.

[0052] Comparative Example 4 The difference between this comparative example and Example 1 is that in the ultra-roughening process, the mixed modifying liquid used in step (3) is replaced by the ultra-roughening solution of step (1).

[0053] According to the super-roughening process recorded in each embodiment and comparative example, the copper surface of the printed circuit board was super-roughened using the corresponding super-roughening solution, and then a solder resist ink with a thickness of 30 μm was coated on the copper surface, first preheated at 80° C. for 2.5 h, and then baked and cured at 150° C. for 50 min, and then referring to the method recorded in "GB / T 9286 Paint and Varnish Cross-cut Test", a tape with an adhesive force of 20 N / 25 mm was used to detect the adhesion rating of the solder resist ink coating, and the results are shown in Table 3.

[0054] Table 3 Adhesion rating

[0055] Combining Examples 1-5 and Comparative Example 1 and Table 3, it can be seen that the adhesion measured in Examples 1-5 is more ideal. This is because the present application performs an ultra-roughening treatment on the printed circuit board twice, and uses tannic acid and chitosan as film-forming components in the second ultra-roughening treatment. The first ultra-roughening treatment and the subsequent pickling provide favorable conditions for the formation of the film layer, and the formation of the film layer fully improves the contact effect between the copper surface and the solder resist ink, thereby overcoming the defects in the related art, and significantly improving the copper surface bonding force, which can fully meet the performance requirements of high-end products.

[0056] Combining Example 1 and Comparative Example 2 and Table 3, it can be seen that the adhesion measured in Example 1 is more ideal, while the adhesion of Comparative Example 2 is poor, indicating that performing super-roughening treatment on the printed circuit board twice in accordance with the method of the present application is helpful to improve the bonding strength of the copper surface.

[0057] Combining Example 1 and Comparative Example 3 and Table 3, it can be seen that the adhesion measured in Example 1 is more ideal, while the adhesion of Comparative Example 3 is poor, indicating that pickling between two super-roughening treatments helps to fully improve the copper surface bonding strength.

[0058] Combining Example 1 and Comparative Example 4 with Table 3, it can be seen that the adhesion measured in Example 1 is more ideal, while the adhesion of Comparative Example 4 is poor. This is because tannic acid and chitosan improve the copper surface bonding strength through film formation, while Comparative Example 4 lacks these two components, resulting in a lower copper surface bonding strength of the solder mask ink.

[0059] Combining Example 5 and Example 6 and Table 3, it can be seen that the adhesion level measured in Example 6 is Level 2, and the adhesive tape selected in the test process of the present application has higher viscosity than the conventional 3M tape, and can still reach Level 2 under this condition, indicating that the printed circuit board already has good copper surface bonding.

[0060] Combining Example 6 and Example 7 with Table 3, it can be seen that the adhesion level measured in Example 7 is level 1. This is because after the sodium hydroxide pretreatment, the oxidized microcrystalline cellulose with more aldehyde groups and easier to cross-link with chitosan is obtained, which improves the film-forming effect of the mixed modified liquid. With the improvement of the film-forming effect, the copper surface bonding force is also improved.

[0061] Combining Example 7, Example 8 and Table 3, it can be seen that the adhesion level measured in Example 8 is level 0, which is further improved on the basis of Example 7. This is because the cyclodextrin polymer is a polymer polymerized with cyclodextrin as a structural unit, and contains a large number of hydroxyl groups in the molecule, which can form a strong hydrogen bond with tannic acid, and can also form hydrogen bonds with chitosan and microcrystalline cellulose. The addition of cyclodextrin polymer can improve the film-forming effect of the mixed modified liquid, thereby helping to improve the copper surface bonding force.

[0062] The above embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments of the present application without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A super-roughening process for a printed circuit board, characterized in that: The following steps are involved: (1) Wash the circuit board with water, then spray the super-roughening solution on the circuit board at 35-45°C, the spraying time is controlled to be 30-120s, and then wash the circuit board to remove the super-roughening solution; in this step, the components of the super-roughening solution include organic copper, formic acid, sodium formate, sodium chloride, a wetting agent, a leveling agent and a regulator; (2) Spray hydrochloric acid on the circuit board, and then wash away the hydrochloric acid on the circuit board with water; (3) Add tannic acid and chitosan to water and dissolve them together, and then mix them with the super-roughening solution of step (1) to obtain a mixed modified solution; immerse the circuit board in the mixed modified solution at 25-35° C., then take it out and dry it, then add the circuit board to glutaraldehyde solution for cross-linking, and then take the circuit board out again and dry it to complete the super-roughening of the printed circuit board.

2. The ultra-roughening process for a printed circuit board according to claim 1, characterized in that: In step (2) of the process, the concentration of hydrochloric acid used is 10-15wt%.

3. The ultra-roughening process for a printed circuit board according to claim 1, characterized in that: In step (3) of the process, oxidized microcrystalline cellulose is also mixed with the ultra-coarsening solution.

4. The ultra-roughening process for a printed circuit board according to claim 3, characterized in that: The oxidized microcrystalline cellulose is prepared according to the following method: Distilled water and sodium periodate are mixed, acidified with sulfuric acid, and then microcrystalline cellulose is added. After being protected from light, the mixture is heated in a water bath while being stirred. After the reaction is completed, ethylene glycol is added, and the unreacted sodium periodate is removed after continued stirring. The mixture is then filtered, and the product is washed with water and dried. The product is then ground and sieved to obtain oxidized microcrystalline cellulose.

5. The ultra-roughening process for a printed circuit board according to claim 4, characterized in that: The microcrystalline cellulose is pretreated before use according to the following method: Weigh microcrystalline cellulose, add it into sodium hydroxide solution and mix it, stir it under heating in a water bath, then filter it and wash it with deionized water, dry the obtained powder, grind it and sieve it, so as to complete the pretreatment of microcrystalline cellulose.

6. The ultra-roughening process for a printed circuit board according to claim 1, characterized in that: In step (3) of the process, the cyclodextrin polymer is also mixed with the ultra-roughening solution.

7. The ultra-roughening process for a printed circuit board according to claim 6, characterized in that: The cyclodextrin polymer is prepared according to the following method: (1) Add cyclodextrin and sodium hydroxide to deionized water, stir to dissolve, heat in a constant temperature water bath, stir under ventilation conditions, and add epichlorohydrin. After the reaction, add acetone in an ice water bath to terminate the reaction; (2) Pour off the supernatant, wash the precipitate with acetone and ethanol in turn, then add water to dissolve the precipitate, and obtain a crude polymer after neutralization. The crude polymer is purified to obtain a cyclodextrin polymer.

8. The ultra-roughening solution according to any one of claims 1 to 7, characterized in that: The super-roughening solution uses water as a solvent and includes components with the following concentrations: 30-50 g / L of organic copper, 80-150 g / L of formic acid, 28-42 g / L of sodium formate, 5-15 g / L of sodium chloride, 230-250 g / L of wetting agent, 3-5 g / L of leveling agent, and 0.1-0.2 g / L of adjusting agent.

9. The ultra-roughening solution according to claim 8, characterized in that: The wetting agent is selected from two of sodium fatty acylamino alkyl sulfate, sodium sulfated ricinoleate, sodium cycloalkane sulfate, and polyethylene imine, and the leveling agent is selected from two of azide polyethylene glycol carboxyl, mannitol, galactitol, and polyethylene glycol.

10. The ultra-roughening solution according to claim 8, characterized in that: The adjusting agent is selected from one of hexadecylamine, sodium ethylenediaminetetramethylenephosphonate, and octadecylamine; and the organic copper is selected from at least one of copper propionate, copper acetate, and copper formate.

Citation Information

Cited By

  • Chromatic aberration control method of Mini LED PCB

    CN120881889A

  • A color difference control method of a mini LED PCB

    CN120881889B